(untitled) (Zaporizhzhia Historical Review, 2021)
The subject matter of the article is the civil registration system development in the first years of Soviet power. The documents under consideration contained information about marriage, birth, divorce, death. Thank to them the new registration system for the first time became a source of information, control and analysis of the civil being for the Soviet government.